Kontribusi Kerukunan Teman Sebaya Dan Kemandirian Belajar Terhadap Prestasi Belajar Siswa Kelas V SD Muhammadiyah 3 Nusukan, Surakarta Tahun Ajaran 2016/2017 - Normalitasari, Pingkan, Dr. Achmad Fathoni, M.Pd (2017)
This research objectives were to examine the contribution of: (1) harmony peers towards learning achievement of grade V of SD Muhammadiyah 3 Nusukan, Surakarta, (2) independent learning towards learning achievement of grade V of SD Muhammadiyah 3 Nusukan, Surakarta, and (3) harmony peers and independent learning towards learning achievement of grade V of SD Muhammadiyah 3 Nusukan, Surakarta. Data collecting techniques used were questionnaires and documentation. This is a quantitative research. Data analysis use multiple linear regression analysis, t test, F test, determination coefficient, also SE and SR, and analysis prerequisite to test for normality and linearity. Based on data analysis, obtained equation: Y = 31,453 + 0,369X1 + 0,264X2. Based on data analysis with significance level of 5%, the following results was obtained: (1) there is a contribution harmony peers towards learning achievement of grade V of SD Muhammadiyah 3 Nusukan, Surakarta, (2) there is a contribution independent learning towards learning achievement of grade V of SD Muhammadiyah 3 Nusukan, Surakarta, and (3) there is a contribution harmony peers and independent learning towards learning achievement of grade V of SD Muhammadiyah 3 Nusukan, Surakarta. The relative contribution of harmony peers was 58,9% and the independent learning was 41,2%. The effective contribution of harmony peers was 16,5% and the independent learning was 11,5%. Keywords: harmony peers, independence of learning, learning achievement